The influence of attitudes on personal computer utilization among knowledge workers: the case of Saudi Arabia - Al-Khaldi, Muhammad A.; Olusegun Wallace, R.S. (Information & management, 1999)
Since the introduction of personal computers (PCs) in the early 1980s, Saudi Arabia has made major investments in PCs to match its rapidly growing economy. As a result, the PC business has become one of the fastest growing sectors in the Kingdom of Saudi Arabia. Our paper reports on the results of a study which investigates the relationships between end-users' attitudes and PC utilization among knowledge workers in the context of Saudi Arabia. To gain a better understanding of the factors that influence the use of PCs, we adopted Triandis' theory which suggests that behavior is determined by attitudes, social norms, habits and expected consequences of behavior. Our study is based on previous efforts to test the theory's validity in Saudi Arabia. Our results suggest that PC utilization is determined by individual attitudes, personal characteristics, such as PC experience, facilitating conditions, such as PC access and social factors. We also observed that respondents to our questionnaire differ in the level of importance they attribute to the factors hypothesized as influencing PC utilization compared to Canadian respondents in a previous study.